The relationship between traditional postnatal care (TPC) and sociodemographic of postnatal mothers in Kota Kinabalu, Sabah, Malaysia - Patricia Sator; Nicholas Tze Ping Pang; Rekaya Anak Vincent Balang; Rosalia Saimon; Mohammad Saffree bin Jeffree; Norkiah Arsat (Bali Medical Journal, 2023)
Background: Traditional Postnatal Care (TPC) is derived from traditional medicines as health practices. The approaches of knowledge and beliefs incorporating plant and manual techniques are applied singularly or in combination to prevent illnesses and maintain well-being. TPC is used widely among the postnatal mother as a self-care for the healing process, both physically and mentally. As part of the nursing management in a community health setting, understanding the different health and wellness approaches and their benefits is part of the early knowledge and skills when delivering care to postnatal mothers. This study aimed to assess the relationship between TPC and sociodemographic data of postnatal mothers in selected study settings to understand more about the types of common TPC practiced within the study setting. Methods: Participants were among the postnatal mothers within one week after delivery and selected purposely based on inclusion criteria. A cross-sectional survey from November 2021 to February 2022 with 178 postnatal mothers completed the distributed questionnaires. The researcher used SPSS version 28.0 to analyse the data. Results:The result showed that the educational background (p=0.001, p<0.05) and household income per month (p=0.001, p<0.05) demonstrated a significant effect concerning postnatal mothers practising and non-practising TPC. Conclusion: This study identified the significant variables of sociodemographic, namely household income and education level. This study’s result is the starting point for the researcher to begin a broader analysis of this title.